Ho Chi Minh's thought on human qualities and development strategy: Content and value - Diem, Vu Kim (The International tax journal, 2025)
The Vietnamese people are the crystallization of Vietnamese culture, embodying the distinct “Vietnamese essence” and “Vietnamese style” in both strengths and weaknesses, preserving the nation's cultural identity across generations. Therefore, in the current era of national renewal, it is essential to develop Vietnamese culture and people in alignment with the demands of sustainable development while actively and proactively integrating into the global community, all while maintaining national cultural identity. More than ever, humans must be placed at the center, regarded as both the goal and the driving force of national development. This article outlines Ho Chi Minh’s thoughts on human qualities and development strategy, focusing on key aspects that should be inherited and applied in the current context of Vietnam.